Improved Photocatalytic Performance of a Novel Fe3O4@SiO2/Bi2SiO5 Hierarchical Nanostructure with Magnetic Recoverability - Xinxin Zhang; Xiaoli Dong; Baiyu Leng; Hongchao Ma; Xiufang Zhang (International Journal of Photoenergy)
Magnetic Fe3O4@SiO2/Bi2SiO5 composites with a novel hierarchical nanostructure were synthesized by sol-gel and hydrothermal methods and were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), and UV-visible diffuse reflectance spectroscopy (UV-vis DRS). It was found that the introduction of Fe3O4@SiO2 could turn the morphology of Bi2SiO5 from close-grained slab to hollow hierarchical architecture with fabric-structure. The Fe3O4@SiO2/Bi2SiO5 composite showed enhanced photodegradation efficiency for the degradation of reactive brilliant red dye (X-3B) in aqueous solution under simulated sunlight irradiation, as compared with that of commercial P25. In addition, the Fe3O4@SiO2/Bi2SiO5 composite exhibited good magnetic recoverability and excellent photocatalytic stability (no obvious activity loss after recycling tests).